The Handbook of Globalisation. - Michie, J (Edward Elgar Publishing, 2003)
Globalization is an issue that has been high in the research agenda for several years, spawning a vast and at times unwiedy literature. A concept often ill-defines, it has generated a plethora of unresolved and fiercely contested questions, the nature of which depends on which side of the ideological divide one stands. With original contributions from the leading commentators in the field and an overarching introduction from the editor, this handbook redefines the concept of globalization with a systematic and thorough examination of the debate.